Pendampingan Hafalan al-Qur’an melalui Metode Finger Qur’an di Pesantren - Ach. Zayyadi; Ruqayyah Miskiyah; Nur Wahyuni Rahmaniyah; Siti Arifah; Wildatul Islamiyah; Nur Aisyah; Wardani Sholehah (GUYUB: Journal of Community Engagement, 2021)
The interest in memorizing al-Qur'an using the Finger Qur'an method at Nurul Jadid Islamic Boarding School shows a significant increase every year. At the same time, the number of teachers of al-Qur'an is not proportional to the number of students who are always increasing. Therefore, this community service is carried out to achieve the ideal ratio of the number of teachers to students, as well as to create a new trainer regeneration every year. This community service program is carried out in two ways, first is the provision of material to teachers and second is assistance in implementing the finger quran method to students. The results of this community service program show that the regeneration of the finger-Quran method teaching staff must be carried out throughout the year. This is due to two things, first, the increasing number of al-Qur'an memorizers every year at Nurul Jadid Islamic Boarding School, Probolinggo; second, there are a number of trainers who have left the pesantren. Through this training and mentoring, the ratio of the number of trainers is balanced and the regeneration process is maintained.